Zarządzanie procesowe w urzędach gmin. Model adaptacji kryteriów dojrzałości procesowej - Flieger, Michał (Wydawnictwo Naukowe UAM, 2016)
Analysis of the changes taking place in public administration, with particular emphasis on the role of communes in the context of current challenges leads to a conclusion that modern communes are forced to take active measures to improve the process of provision of services. To this end, authorities of communes can implement process management. Th is process promotes implementation of the developed model, which facilitates the achievement of process maturity by the local offi ces. Local offi ces may also use the chosen modern management concepts that support implementation and management of the local process offi ce, while the examples cited illustrate the practical application potential. An in-depth analysis of the application of process management in today’s local offi ces, based on research conducted in the communes of the Wielkopolska region, shows that this is still an instrument rarely used in practice.

W pracy zanalizowano przemiany zachodzące w administracji publicznej, ze szczególnym uwzględnieniem roli gmin, zmuszonych do podejmowania aktywnych działań usprawniających proces świadczenia usług publicznych ze względu na rosnące potrzeby odbiorców tych usług oraz procesy konkurencyjne, w których gminy uczestniczą. W celu usprawnienia działania urzędów gmin autor proponuje własny model wdrażania zarządzania procesowego ułatwiający urzędom osiągnięcie dojrzałości procesowej. Wskazuje na możliwości wykorzystania wybranych współczesnych koncepcji zarządzania wspierających wdrażanie i zarządzanie urzędem procesowym, podaje przykłady praktyczne, a na końcu przedstawia pogłębioną analizę zastosowania zarządzania procesowego we współczesnych urzędach gmin, opierając się na badaniach przeprowadzonych w gminach województwa wielkopolskiego.
Process management in the local offi ces. Model of adaptation of the process maturity criteria
Keywords: zarządzanie procesowe; zarządzanie urzędem gminy; zarządzanie publiczne; model; dojrzałość procesowa